Parenting Styles in Modern Families in the Digital Age: A Literature Review - Andi Mekar Sari Tenri Olle (Universitas Negeri Gorontalo, 2026)
The advancement of digital technology has significantly influenced parenting patterns in modern families. This study aims to analyze how parents adapt their parenting strategies to address the challenges of the digital era through a systematic literature review of 30 national and international journals. The method employed is a systematic literature study using content analysis techniques to identify key patterns, challenges, and parenting strategies. The results show that the authoritative parenting style is the most commonly applied approach, characterized by a combination of strict supervision and guided freedom for children. Major challenges faced by modern families include gadget addiction, moral degradation, shifting social values, and emotional neglect. Effective adaptation strategies include parental accompaniment in digital media usage, setting limits on screen time, strengthening character education based on cultural and religious values, and fostering strong collaboration between families, schools, and communities. The practical implication of this study highlights the importance of enhancing digital literacy among both parents and children, as well as the need for adaptive parenting education programs in the era of digital transformation. Further empirical research is recommended to examine the effectiveness of parenting styles in diverse family contexts. Keywords: parenting, modern family, digital era